2015
DOI: 10.1111/ijd.12623
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome in Moroccan patients with psoriasis

Abstract: Metabolic syndrome is an important comorbidity in patients with psoriasis, and vigilance and enhanced screening may be important in this population, especially patients with severe disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 25 publications
3
15
0
Order By: Relevance
“…In contrast, we could not confirm this correlation in our study. In comparison with data from the literature, we partly recorded lower rates of comorbid diseases in our series [35][36][37] . An explanation for the lower rates detected may be that 64.8% of the patients received Fumaderm ® as a first-line therapy, which means that the patients were in comparatively early stages of the disease.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…In contrast, we could not confirm this correlation in our study. In comparison with data from the literature, we partly recorded lower rates of comorbid diseases in our series [35][36][37] . An explanation for the lower rates detected may be that 64.8% of the patients received Fumaderm ® as a first-line therapy, which means that the patients were in comparatively early stages of the disease.…”
Section: Discussionsupporting
confidence: 68%
“…An explanation for the lower rates detected may be that 64.8% of the patients received Fumaderm ® as a first-line therapy, which means that the patients were in comparatively early stages of the disease. It is well known that the rate of comorbidity increases with severity of psoriasis [36,37] .…”
Section: Discussionmentioning
confidence: 99%
“…Whereas, the opposite situation was noted when comparing the diabetic and nondiabetic patients. Observations conducted by two independent research teams indicate that systemic diseases concurrent with psoriasis contribute to more intensified psoriatic symptoms (Itani, Arabi, Harb, Hmazeh, & Kibbi, ; Meziane et al, ). It may result from the disproportion between the number of patients with Diabetes 2 when compared with the number of patients without it.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas, the opposite situation was noted when comparing the diabetic and nondiabetic patients. Observations conducted by two independent research teams indicate that systemic diseases concurrent with psoriasis contribute to more intensified psoriatic symptoms (Itani, Arabi, Harb, Hmazeh, & Kibbi, 2016;Meziane et al, 2016 Gisondi, Del Giglio, and Di Francesco (2008) states that in the group of obese psoriatic patients treated using CsA, reduced body weight (through the use of a low-calorie diet) improves response to the medicine.…”
Section: Discussionmentioning
confidence: 99%
“…Many of these studies were looking for biomarkers of disease – for example, TNF-α, IL-6, IL-8, IL-17A, soluble TNF receptors-1, and lipocalin 2 5,6. Meziane et al reported that abdominal obesity and dyslipidemia were metabolic factors significantly related to psoriasis, and hypertension, diabetes, increased levels of triglycerides, and high-density lipoprotein cholesterol were associated with the severity of psoriasis in Moroccan patients with psoriasis 7. However, so far there has been no specific research into detailed systemic abnormalities in psoriatic patients.…”
Section: Introductionmentioning
confidence: 99%